(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This article expresses concern over the current environmental crisis and offers a solution using the Maqasidi interpretation to address environmental conservation. The teachings consistently echoed in Islamic sources are that conservation is for the greater good, not the greater good. Given the crucial role of Islamic teachings in encouraging its followers toward environmental conservation, an affirmation and commitment from each individual is needed to prioritize the common good (mashalih mursalah), specifically environmental preservation. A commendable form of shared commitment is the imposition of sanctions and deterrents on perpetrators of environmental destruction, which ultimately lead to the common good. This will enable the intent and purpose of sharia to be realized.